Ophiostomatoid fungi associated with mites phoretic on bark beetles in Qinghai, China - Runlei Chang; Tuan A. Duong; Stephen J. Taerum; Michael J. Wingfield; XuDong Zhou; Z. Wilhelm de Beer (IMA Fungus, 2020)
Abstract Bark beetle galleries are complex ecosystems where many microbes and other arthropods co-exist with the beetles. Fungi isolated from these galleries are often referred to as ‘beetle associates’, but the nature of these associations are poorly understood. The possibility that many of these fungi might in fact be mite associates is often overlooked. Several recent studies explored the diversity of fungi from conifer-infesting bark beetles and their galleries in China, but only one study considered phoretic mites and their fungi from conifer-infesting bark beetles in Yunnan, southwestern China. We studied the mites and fungi from galleries of four spruce-infesting bark beetle species in the high altitude forests of Qinghai province, western China. Mites were identified based on morphological characteristics, and fungi based on DNA sequences of four gene regions. In total, 173 mite individuals were collected belonging to 18 species in 11 genera. A total of 135 fungal isolates were obtained from the mites, representing 14 taxa from the Ophiostomatales. The most frequently isolated fungus was Ophiostoma nitidum, which represented 23.5% of the total isolates. More fungal species were found from fewer mites and bark beetle species than from the study in Yunnan. Although we could not elucidate the exact nature of interactions between mites and their fungi, our results re-enforce that these organisms should not be ignored in pest risk assessments of bark beetles, that often focus only on the beetles and their fungi. Three new species are described: Grosmannia zekuensis, O. manchongi, and O. kunlunense spp. nov., and our data revealed that O. typographi, recently described from China, is a synonym of O. ainoae.